The Impact of Fiscal Policy on Inequality and Poverty in Zambia - De La Fuente, Alejandro; Rosales, Manuel; Jellema, Jon (World Bank, Washington, DC, 2017)
This study assesses the redistributive impact of fiscal policy––and its individual elements––in Zambia. Zambia's 2015 fiscal policy reduces inequality; the largest reduction is created by in-kind public service expenditures on education. However, fiscal policy also increases poverty in three ways: (1) there is a relatively low level of targeted, direct-transfer spending; (2) energy subsidies, which do not reach many poor households, absorb a large share of expenditures; and (3) tax instruments create a burden greater than what is received as direct or indirect benefits from subsidies or direct transfers. The number of poor and vulnerable individuals who experience net cash subtractions from their incomes is greater than the number of poor and vulnerable individuals who experience net additions. Eliminating subsidy spending while compensating poor households would help fiscal policy achieve poverty reduction and even greater inequality reduction. If subsidies on fuel, electricity, and agricultural inputs were eliminated without any compensatory mechanism, such as an increase in the Social Cash Transfer program's coverage and benefit levels, the impact of fiscal policy on poverty would likely be muted. In 2015, Zambia exempted over 80 percent of the average household's consumption basket. However, value-added tax exemptions imply only that some portion of value-added is not taxed, and so do not entirely eliminate a value-added tax burden. A more efficient way to deliver net benefits to poor and vulnerable households is through targeted cash transfers at a scale large enough to compensate for the burden created across households by value-added tax and other indirect taxes.